MEMAHAMI KOMUNIKASI INTERPERSONAL ORANG TUA DAN GURU DALAM MEMBANGUN KETERAMPILAN SOSIAL (SOCIAL SKILLS) PADA ANAK AUTIS - Arlini Agestia Pangestika; Sri Budi Lestari (Interaksi Online, 2017)
Autism is a developmental disorder characterized by disruption in communication and limited social interaction. This limitation makes the importance of the role of parents and teachers in building social skills in autism children to help them interact with others and organize themselves in certain social situations. This research focuses to describe the interpersonal communication performed by parents and teachers in the process of building social skills of autism children that using Symbolic Interaction Theory (George Herbert Mead) which explains that behavior can be formed through interaction, and Social Learning Theory (Albert Bandura) which explains that people can form behavior based on observation result. This research used descriptive qualitative type of research and phenomenology approach, and the research resource are parents who have autism children as much as three informants, and teachers who special educate autism children as much as two informants. The results showed that the interpersonal communication performed by parents and teachers to autism children is built through the closeness that get in by openness, attention, empathy, equality, and supportive when communicating, this closeness is used to build social skills through interpersonal persuasion in autism children. The understanding of parents and teachers to verbal and nonverbal messages of autism children becomes very important because it will be help the communication process between parents, teachers, and autism children.Then the belief of parents and teachers to the ability of autism children is the one of the factors that encourage the development of social skills, because autism children will be more flexible to develop their behavior according to ability possessed. In addition, rewarding and positive assessment to autism children also provide their motivation and confidence to form positive behavior, while punishment will provide an understanding to autism children that negative behavior should be avoided. Therefore, parents and teachers should have a commitment in educating autism children by giving examples of positive behaviors and practice together with them to be more easily observed and perfomed by autism children, because parents and teachers have an important role to provided awareness about social norms in society obtained through the formation of social skills in autism children.